1976
DOI: 10.1152/jn.1976.39.4.816
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoreceptors for near-field water displacements in crayfish

Abstract: 1. Mechanosensory hairs on the surface of the crayfish telson are dually innervated, one sensory cell responding to headward, the other to tailward deflection of the hair. The average conduction velocity of headward elements was 0.8 m/s (variance 0.08) and of tailward elements 1.2 m/s (variance 0.19). In a frequency range from 0.05 to 200 Hz, thresholds were lowest near 20 Hz: 0.08 mum (pp) for headward-sensitive and 0.1 mum (pp) for tailward-sensitive cells. 2. The receptors are displacement sensitive since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(86 citation statements)
references
References 0 publications
6
78
0
Order By: Relevance
“…Data from 18 neurons have shown that at 10 Hz their mean threshold to sinusoidal oscillations of the fluid surface above the associated sensillum was 0.02 m (SD ϭ Ϯ0.009). Moreover, as do those displacements associated with the tailfan feathered sensilla (18), displacements of increasing velocity generate monotonic increases in mean impulse frequency up to saturation near 1,000 m/sec (Fig. 1F).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Data from 18 neurons have shown that at 10 Hz their mean threshold to sinusoidal oscillations of the fluid surface above the associated sensillum was 0.02 m (SD ϭ Ϯ0.009). Moreover, as do those displacements associated with the tailfan feathered sensilla (18), displacements of increasing velocity generate monotonic increases in mean impulse frequency up to saturation near 1,000 m/sec (Fig. 1F).…”
Section: Resultsmentioning
confidence: 61%
“…1C). Like feathered sensilla described on the tailfan (18) and earlier on the cephalothorax (20), each antennular sensillum is supplied by two sensory neurons that have opposite directional preferences in their respective sensitivity to displacements. Typical electrophysiological recordings from two standing feathered sensilla are shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, a neural response was found when the sensory hairs on crustaceans were stimulated by flows as slow as 0.006 cm s -1 (Wiese 1976;Bleckmann 1994).…”
Section: Perception Of the Flowmentioning
confidence: 99%
“…For example, the sensory hairs of crustaceans can number many thousands and are distributed across the whole body-length. The velocity threshold of hairs may be as low as 0.006 cm s -1 with each hair sampling at a rate of up to 150 Hz (Wiese 1976;Breithaupt and Tautz 1990). Therefore, crustaceans such as crayfish in rivers, may be able to gain detailed information about the turbulent characteristics of flow, and process substantially more than depth-and reach-averaged velocity information.…”
Section: The Need For Information At Relevant Scales and How To Obtaimentioning
confidence: 99%